2020
DOI: 10.1109/access.2020.2983134
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for in-Line Control of Moisture Content During Green Tea Processing

Abstract: During preliminary tea processing, moisture content is an important consideration affecting the tea quality. Traditionally, the moisture content of tea leaves was manually controlled by the joint action of multiple processing units, and maintaining stability was difficult. In this paper, a multi-unit collaborative strategy was proposed for controlling moisture content in preliminary tea processing. Multivariate methods including polynomial regression, radical basis function neural network (RBFNN), and least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition, drying preserved the phytochemical constituents of tea leaves [14]. Previous report showed that high moisture content supported microbial growth and triggered the deterioration of tea phytochemicals [21]. Wang et al [22] reported that a decrease in moisture content tea and enhanced tea aroma.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, drying preserved the phytochemical constituents of tea leaves [14]. Previous report showed that high moisture content supported microbial growth and triggered the deterioration of tea phytochemicals [21]. Wang et al [22] reported that a decrease in moisture content tea and enhanced tea aroma.…”
Section: Resultsmentioning
confidence: 95%
“…The MC of the tea samples was 5.72% according to the drying method; they were divided into several portions of 2 kg each and placed in a sealed bag for use. Since the MC of tea before drying is approximately 55%, the MC range was set to 5.7-55.2% [20,21] and the MC gradient was set to about 2%. The MC formula was used to calculate the amount of distilled water that needed to be sprayed on each sample [22].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Tea production involves multiple processing procedures, drying being is the last process. Owing to the loss of water and consolidation of the shape of the tea leaves, subtle reactions occur in the internal components of tea, which is essential to develop color, aroma, and taste (Li, Ai, Yu, Chen, & Ni, 2019;Ye, Gong, Gui, Teng, & Gao, 2019;Zhao, Chen, Chen, Xie, & Peng, 2020). Because traditional tea drying processes are based on the subjective judgment of workers and masters to ensure high tea quality, it lacks stability.…”
Section: Introductionmentioning
confidence: 99%